2020
DOI: 10.1186/s12929-019-0597-7
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of granulocyte-colony stimulating factor (G-CSF) as a novel therapy for stroke in a mouse model

Abstract: Background: The FDA approved drug granulocyte-colony stimulating factor (G-CSF) displays anti-apoptotic and immunomodulatory properties with neurogenesis and angiogenic functions. It is known to demonstrate neuroprotective mechanisms against ischemic global stroke. Autophagy is a method for the degradation of intracellular components and in particular, unrestrained autophagy may lead to uncontrolled digestion of affected neurons as well as neuronal death in cerebral ischemia. Mitochondrial dynamics is vital fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 59 publications
3
35
0
Order By: Relevance
“…The protective effect of the single dose of hG-CSF gene therapy was significant at 4 days and 7 days after ischemia, evident from functional improvements determined by corner test and locomotor activity. This evidence is further supported by our previous study on the protective mechanism of the G-CSF protein [ 52 ] and provided added credence to the efficacy of hG-CSF gene therapy.…”
Section: Discussionsupporting
confidence: 75%
“…The protective effect of the single dose of hG-CSF gene therapy was significant at 4 days and 7 days after ischemia, evident from functional improvements determined by corner test and locomotor activity. This evidence is further supported by our previous study on the protective mechanism of the G-CSF protein [ 52 ] and provided added credence to the efficacy of hG-CSF gene therapy.…”
Section: Discussionsupporting
confidence: 75%
“…Activation of BAX and BAD also promote MOMP [ 88 ]. The BCL-2 family proteins are key regulators of MOMP and play critical role in the intrinsic apoptotic pathway, classified into anti-apoptotic (Bcl-2, Bcl-xl, Bcl-w) and pro-apoptotic (Bax, Bak, Bim, Bid, Bad) [ 45 ]. The increased expression of pro-apoptotic markers is also influenced by the hormones involved in the pituitary–adrenal response [ 89 ], while in the extrinsic pathway, binding ligands to death receptors (TNF-α, Fas, TRAIL, etc.)…”
Section: Regulation Of Cytokines and Apoptosis By G-csf In Neonatal Hmentioning
confidence: 99%
“…G-CSF administration downregulates GSK-3ß activity, resulting in reduced neuronal cell death, apoptosis, and infarct volume, as well as upregulating anti-apoptotic protein Bcl-2 expression levels [ 45 , 77 ]. Our previous study has demonstrated that increased Bax expression levels and cleaved caspase-3 (CC3) activation were attenuated significantly by G-CSF treatment and simultaneously increasing BCL-2 expression levels that were decreased following HI-induced injury.…”
Section: Regulation Of Cytokines and Apoptosis By G-csf In Neonatal Hmentioning
confidence: 99%
See 1 more Smart Citation
“…G-CSF (granulocyte-colony stimulating factor) is an endogenous ligand in the CNS that displays several important functions including anti-apoptotic activity, immunomodulatory action, stimulates neurogenesis, and angiogenic capabilities. G-CSF treatment exerts neuroprotective effects on damaged neurons by decreasing pro-apoptotic proteins and increasing of antiapoptotic proteins, both reducing acute neuronal degeneration and adding to long-term plasticity after cerebral ischemia [ 88 , 89 ]. Balseanu et al, demonstrated in a stroke rat model that daily intravenous injection of G-CSF led to robust and consistent improvement of neurological functions, which in a combination with a single intravenous administration of mesenchymal stromal cells (MSC) increased the neurogenesis in the subventricular zone and improved microvessel density in the formerly infarct core and perilesional area of treated aged rats, but had no beneficial effect on the infarct volume or mortality [ 90 ].…”
Section: Gene Therapy For Strokementioning
confidence: 99%